Pola asuh ibu sebagai faktor risiko kejadian kurang energi protein (KEP) pada anak balita - Adni Abdul Razak; I Made Alit Gunawan; R Dwi Budiningsari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Protein energy deficiency (PED) is one of nutrition disorders which happen to children under-five years. According to data of nutritional status examination result 2005 and 2006, the prevalence of PED at the Province of Sulawesi Tengah was 30.61% and 30.84%, whereas at District of Morowali was 11% and 11.6%. Lots of factors cause malnutrition among children under five, among others is imbalanced nutrient intake, infection, and rearing pattern of mothers comprising care and food supply.Objective: To identify rearing pattern of mothers as risk factor for the prevalence of PED in children under five. Method: This was an observational study with case control study design. Population and samples of the study were children under five suffering from PED as indicated from anthropometric standard weight for age according to standard of WHO National Child Health Standard (NCHS), i.e. < -2 elementary school to ≥ -3 elementary school. The controls were children under five who did not suffer from PED. Respondents consisted of mothers of children who had PED and did not have PED that fulfilled inclusion and exclusion criteria. The variables observed were rearing pattern, infection as confounding variable and nutritional status. Nutritional status of children with PED and without PED was processed using index of weight for age against standard of WHO-NCHS. Chi-square and odds ratio were used to identify rearing pattern as risk factor for PED.Results: The result of the study showed that there were 23 mothers (57.5%) practicing poor rearing pattern in children with PED and there were 35 mothers (87.5%) practicing good rearing pattern in children without PED. The result of statistical test showed p < 0.05, i.e. p = 0.001, so there was significant difference in rearing pattern of mothers which consisted of knowledge, attitude and practice in the care and food supply of children under five.Conclusion: Poor rearing pattern of mothers brought greater risk for children with PED than good rearing pattern in the care and food supply of children under-five.